Cured of Primary Bone Cancer, But at What Cost: A Qualitative Study of Functional Impairment and Lost Opportunities. (9th April 2015) - Fauske, Lena; Bruland, Oyvind S.; Grov, Ellen Karine; Bondevik, Hilde
Abstract : Purpose . Our study aims to explore how former cancer patients experience physical and psychosocial late effects 3–7 years after they underwent treatment for primary bone sarcoma in the hip/pelvic region. A qualitative, phenomenological, and hermeneutic design was applied. Methods . Sarcoma survivors (n = 10 ) previously treated at Oslo University Hospital, Norwegian Radium Hospital were selected to participate. In-depth and semistructured interviews were conducted. The interviews were analysed using inductive thematic analysis. Results . The participants reported that the late effects had three core spheres of impact: "their current daily life, " "their future opportunities, " and "their identity." They expressed negative changes in activity, increased dependence on others, and exclusion from participation in different areas. Their daily life, work, sports activities, and social life were all affected. Several of their experiences are similar to those described by people with functional impairment or disability. Conclusion . Patients cured of bone cancer in the hip/pelvic region pay a significant price in terms of functional impairment, practical challenges, exclusion from important aspects of life, and loss of previous identity. It is important to appreciate this in order to help bone cancer survivors who struggle to reorient their life and build a secure new identity.